Expanding the Market for MSMEs Keripik Tempe in Denpasar City through Digital Marketing Strategies with an Empowerment-Based PAR Approach - Wardani, Kadek Devi Kalfika Anggria; Artnat, Diwan Sanjaya; Gorda, Anak Agung Ngurah Eddy Supriyadinata (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This Community Service activity aims to expand the marketing scope of the MSME keripik tempe "Crackels" by providing materials on the importance of utilizing digital marketing and Instagram as a platform for business product promotion. Method: The activity was conducted using the Participatory Action Research (PAR) method, involving several stages such as planning, implementation, and evaluation. Practical Applications: The practical application of this activity included the direct implementation of digital marketing strategies by MSME actors, such as creating and managing Instagram accounts for product marketing. The MSME participants learned how to create engaging content and follow trends to increase the appeal of their products, resulting in a significant increase in followers and sales. Additionally, they utilized other applications like WhatsApp to support promotions, making marketing efforts more effective and efficient. Conclusion: This community program successfully increased the number of followers and sales for the MSME keripik tempe "Crackels" beyond the Renon area. For sustainability, additional activities such as creative content training, advanced digital marketing strategies, and regular evaluations are needed to help MSMEs effectively utilize digital technology and marketing strategies.